L'harmonie des Sirènes du pythagorisme ancien à Platon - Viltanioti, Irini-Fotini (De Gruyter, 2015)
The Pythagorean theory of the "Harmony of the Spheres" has been influential in the history of philosophy and science. While much ink has been spilt over its scientific implications, its mythological formulation has not yet received serious scholarly attention. This groundbreaking book fills that gap by offering a sustained study of the theory`s mythological rendition in Plato`s Republic and in Iamblichus` On the Pythagorean Way of Life.